2015
DOI: 10.1097/coc.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Impact of Preoperative Chemoradiotherapy on Outcome and Postoperative Complications in Esophageal Cancer Patients

Abstract: Preoperative chemoradiotherapy has emerged in the treatment of esophageal cancer as a means to down-stage tumors, improve local control, and possibly improve overall survival. However, there are concerns that postoperative complications may be increased by preoperative chemoradiotherapy. We review the rationale for preoperative chemoradiotherapy. We review the literature to identify the potential postoperative complications, the risk of complications, and the risk factors for complications. Although individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Neoadjuvant chemoradiotherapy has been frequently correlated with increased pulmonary complications, 5,14,25 whereas the pulmonary complication rates were similar between groups in the present study. It has been suggested that the means of radiotherapy administration and radiotherapy fractionation may minimize lung toxicity and low-dose volume may be more important in the prevention of pulmonary complications than high-dose volume.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Neoadjuvant chemoradiotherapy has been frequently correlated with increased pulmonary complications, 5,14,25 whereas the pulmonary complication rates were similar between groups in the present study. It has been suggested that the means of radiotherapy administration and radiotherapy fractionation may minimize lung toxicity and low-dose volume may be more important in the prevention of pulmonary complications than high-dose volume.…”
Section: Discussionsupporting
confidence: 60%
“…19 As reported by others and confirmed in the present large cohort study, high ASA scores, 7 supracarinal tumor location, and cervical anastomosis 9 were independent predictors of AL but not NCRT. 5,13,14,26,27 Our results suggest that NCRT does not have an impact on 90-day postoperative mortality and overall morbidity, including pulmonary complications, but does increase chylothorax rates with a trend toward more cardiovascular and thromboembolic complications. Consequently, our results suggest that NCRT does not preclude an intrathoracic anastomosis for infracarinal tumors.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Compared with SA, neoadjuvant therapy may add to the risk of toxicity. The potential complications, which included pneumonia, acute respiratory distress syndrome, anastomotic leakage, and cardiac complications, were mainly caused by radiotherapy . In a study of Bosch et al ., a significant increase in cardiopulmonary complications was observed in the neoadjuvant therapy group.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, neoadjuvant chemoradiotherapy (NCRT) has gradually gained clinical acceptance, but has the potential for degrading the staging of primary tumors, and is thus controversial, especially neoadjuvant radiotherapy (NRT) . Though NRT can reduce the size of a local tumor and make it possible to perform surgery, NRT might also increase the risk of postoperative complications, which are associated with a poor prognosis . Furthermore, the stage of non‐cervical esophageal cancer that would result in a greater benefit from NRT has not been established, and no research based on a large population has determined the correlation between NRT and prognosis in patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%